Gestion de la pandémie COVID-19 au Sénégal - Diouf, Ibrahima (Me´decine De Catastrophe, Urgences Collectives, 2020)
The COVID-19 pandemic that began in December 2019 in the city of Wuhan in China reached Senegal on March 02, 2020 through a case imported from Europe. The country began the response based on the experience of the Ebola fever epidemic and relying on the ONE HEALTH approach set out in the national health security plan. Thus, although it is multisectoral, the Ministry of Health played a leading role at the start of the coordinated response through its various branches, including the Health Emergency Operations Center. Concomitantly with this health response, mechanisms have been developed in the Economic and Social Resilience Program in order to ensure the continuity of operations in this long-term fight with consequences in all sectors. As COVID-19 pandemic evolves, the response mobilizes significant resources facilitated by the commitment of the highest authorities and following an adaptive strategy, which has led to convincing results.